1987
DOI: 10.1021/j100308a021
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Solvation of the Intramolecular-Charge-Transfer Molecule p-(Dimethylamino)benzonitrile

Abstract: This paper presents a systematic study of gas-phase p-(7V,7V-dimethylamino)benzonitrile (DMABN) both in a supersonic jet expansion and in a thermalized vapor. From the jet studies, the excitedand ground-state vibrational spectra of the isolated molecule are resolved, and the spectroscopy of the stoichiometric complex with water, methanol, ammonia, and acetonitrile in the beam is reported. It is concluded that 1:1 complexes are not sufficient for the local perturbation to cause charge separation. At higher temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
40
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 42 publications
(5 reference statements)
7
40
0
Order By: Relevance
“…Since the solvent system remains the same, it can be concluded that it is the torsional angle which directly influences Ap,. This observation is in agreement with the gas phase measurements, which clearly indicate that CT in the excited state is linked to the twisting of the phenyl-dimethylamino bond (6,7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Since the solvent system remains the same, it can be concluded that it is the torsional angle which directly influences Ap,. This observation is in agreement with the gas phase measurements, which clearly indicate that CT in the excited state is linked to the twisting of the phenyl-dimethylamino bond (6,7).…”
Section: Discussionsupporting
confidence: 92%
“…The fact that solvent plays a direct role comes from the following experiments. Experimental studies on DMABN in a supersonic jet expansion show that isolated molecules show only F, fluorescence and hence do not undergo twisting (6). Further evidence from spectroscopic and picosecond studies indicates that a short-range coupling interaction between a specific number of solvent molecules and the solute, either in the ground or exited state, is essential for TICT formation (4e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8] The fundamental issues associated with the dual fluorescence of DMABN relate to the reaction pathway that connects the two states [1,2,4,7,[9][10][11][12] and the geometrical structure of the emitting ICT state. [22] We have now employed cucurbit[n]urils (CBn, n = 5-8, Scheme 1) as water-soluble macrocyclic host molecules, which are unique due to their high symmetry, rigidity, chemical inertness, and exceptional binding strengths. Experimental investigations involving differently substituted or structurally confined derivatives of DMABN, [13] as well as in media of different polarity and viscosity, [8,9,17] including the gas phase, [10] micelles, [18] solvent clusters, and supramolecular host cavities, [19][20][21] have invariably afforded evidence for the well-known dual emission, with the LE band centered around 350 nm and the ICT band around 450-500 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Both electron (25)(26)(27)(28) and proton transfer (20)(21)(22)29) processes were also studied, elucidating for the former one of the classics for Mulliken's dative bonded complexes, that of benzene-iodine, and for the latter the dynamics of single and double proton transfer. With mass selection, we investigated ionic clusters, the premier being solvated electrons (30) and dioxygen anions (31)(32)(33); both are important in biological activities.…”
mentioning
confidence: 99%